2015
DOI: 10.1590/s0100-204x2015000500006
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de genótipos de feijão-caupi para o mercado de vagens e grãos verdes

Abstract: Resumo -O objetivo deste trabalho foi avaliar a variabilidade de genótipos de feijão-caupi e selecionar aqueles com potencial para o mercado de vagens e grãos verdes. Em 2012, foram avaliados 16 genótipos em dois experimentos (sequeiro e irrigado), em delineamento de blocos ao acaso, com quatro repetições. Foram avaliados os caracteres: número de dias para o início da floração, comprimento de vagem verde, número de grãos por vagem verde, massa de cem grãos verdes, produtividade de vagens verdes, produtividade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
3
7
1
2
Order By: Relevance
“…The average immature grain yield was 1,599 kg ha -1 (Table 3), which was considered low, probably because most of the trials were conducted under irrigation and there was overgrowth during the production period in some of them. This average was lower than those of 1,957 and 2,390 kg ha -1 found by Sousa et al (2015) for rainfed and irrigated cultivation, respectively, when evaluating 16 cowpea genotypes in the municipality of Teresina, in the state of Piauí, Brazil, and than that of 2,827 kg ha -1 reported by Freitas et al (2016) for irrigated cultivation, when studying 12 cowpea genotypes under the soil and climate conditions of the municipality of Mossoró, in the state of Rio Grande do Norte. However, the average immature grain yield obtained in the present study was superior to that of 1,353 kg ha -1 observed by Silva et al (2013) for rainfed cultivation, when evaluating 8 cowpea cultivars under the edaphoclimatic conditions of the municipality of Serra Talhada, in the state of Pernambuco, Brazil.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…The average immature grain yield was 1,599 kg ha -1 (Table 3), which was considered low, probably because most of the trials were conducted under irrigation and there was overgrowth during the production period in some of them. This average was lower than those of 1,957 and 2,390 kg ha -1 found by Sousa et al (2015) for rainfed and irrigated cultivation, respectively, when evaluating 16 cowpea genotypes in the municipality of Teresina, in the state of Piauí, Brazil, and than that of 2,827 kg ha -1 reported by Freitas et al (2016) for irrigated cultivation, when studying 12 cowpea genotypes under the soil and climate conditions of the municipality of Mossoró, in the state of Rio Grande do Norte. However, the average immature grain yield obtained in the present study was superior to that of 1,353 kg ha -1 observed by Silva et al (2013) for rainfed cultivation, when evaluating 8 cowpea cultivars under the edaphoclimatic conditions of the municipality of Serra Talhada, in the state of Pernambuco, Brazil.…”
Section: Resultscontrasting
confidence: 64%
“…The market for immature cowpea is highly promising, as it represents an important source of employment and income around the producing region (Freire Filho, 2011;Rocha et al, 2017a). However, it is currently characterized by the inexistence of improved cultivars and by the cultivation of landraces, generally with a low grain yield, late maturation cycle, and low disease resistance (Sousa et al, 2015). In addition, the pod is usually harvested at a stage with about 60 to 70% moisture (Sousa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the Madalena assay, there was a significant difference (P < 0.01) for six of the seven characters evaluated. This evidences the presence of genotypic differences among the cowpea landraces evaluated in the study and, therefore, the possibility of gains with the selection, as found in other studies of this nature (LOCATELLI et al, 2014;SANTOS et al, 2014a;SOUSA et al, 2015). The varieties presented similar performances regarding the cycle in the condition of Madalena, with an approximate average of 78 days.…”
Section: Resultssupporting
confidence: 82%
“…O feijão-caupi, espécie de alto valor nutritivo, proteico, é caracterizado por apresentar uma grande adaptabilidade nas regiões tropicais (BARROS et al, 2013). Isso se dá devido a sua grande variabilidade genética, e consequentemente versatilidade, justificando assim a sua utilização nos mais diversos sistemas de produção e finalidades (SOUZA et al, 2015).…”
Section: Fundamentação Teóricaunclassified